Haiti : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criterion and Augmentation of Access; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Haiti. (IMF Staff Country Reports; Country Report ;, 2009)
The staff report for Haiti's Fourth Review under the Three-Year Arrangement, and request for Waiver of Performance Criterion and Augmentation of Access is examined. The financial system, which has not been significantly affected by the financial crisis, remains sound. External credit lines are small and mostly trade related. Indicators of banking sector soundness remained broadly satisfactory with increased net profits and declining nonperforming loans, although the financial position of two small banks had weakened further.